Replacement Of Sand By Quarry Dust In Concrete - Waleed Bark Mesari (School of Environmental Engineering, University Malaysia Perlis, 2016)
To determine the physical properties of quarry dust concrete. To determine the engineering properties of quarry dust concrete. To determine the optimum percentage of quarry dust as replacement the sand and comparison stander mix.